Surgical management of aphakia. Issue 12 (December 2022) - Cheng, Kelvin K.W.; Tint, Naing L.; Sharp, John; Alexander, Philip
Abstract : A review describing various options of surgical management of aphakia. Advantages and disadvantages of each technique is described and a clinical decision tree is proposed. Abstract : Despite the safety and efficacy of cataract surgery, intraoperative complications can hamper the ability to place an intraocular lens in the capsular bag. With vast numbers of cataract surgeries performed daily, complications occur often enough that every ophthalmologist should be equipped with techniques to manage aphakia. Medical management of aphakia used to be commonplace but these techniques have their disadvantages including thick bulky lenses, poor cosmesis, and aniseikonia. Surgical management of aphakia overcomes these disadvantages and offers patients the possibility of a spectacle and contact lens-free lifestyle. This article reviews the various options of surgical management of aphakia and their advantages and disadvantages. Comparison of outcomes between techniques and a protocol for deciding between techniques is presented.